Carbon Dioxide Provocation of Anxiety and Respiratory Response in Bipolar Disorder - MacKinnon, Dean F (2006)
BACKGROUND: Frequent bipolar/panic comorbidity implies bipolar individuals may experience CO2-provoked anxiety and changes in respiratory patterns similar to those experienced by individuals with panic disorder. METHODS: 16 euthymic bipolar individuals breathed air and air combined with 5% CO2 for 15 minutes each. Respiratory and subjective anxiety measures were collected. RESULTS: On CO2 subjects were more anxious and breathed more deeply and rapidly than with air; the degree of increase in anxiety attributable to CO2 was directly correlated with the degree of increase in minute ventilation. Five individuals were assessed as having a panic attack. Panic response to CO2 was predicted by the degree of anxiety experienced with air alone. CONCLUSIONS: Comparison with the results of similar panic studies shows bipolar disorder is associated with enhanced respiratory response to CO2. Hypersensitivity to CO2 among bipolar individuals suggests a possible pathological mechanism common to both bipolar and panic disorders. These preliminary data support the expanded application of CO2 challenges in bipolar subjects.